Evaluation of subchronic toxicity of lactobacillus paracasei hii03 fermented morinda citrifolia (Noni) fruit juice - Chaiyavat Chaiyasut (2018)
© 2018 The Authors. Published by Innovare Academic Sciences Pvt Ltd. Objective: The present study evaluated the subchronic toxicity of Lactobacillus paracasei mediated fermented Morinda citrifolia (Noni) juice (FMJ) using Sprague Dawley rat as a model system. Methods: FMJ was prepared. The microbial load and pH of FMJ during fermentation were measured by a plating method and using pH meter, respectively. The healthy rats were supplemented with different doses of FMJ for 60 days. The changes in body weight of the animals were measured during FMJ intervention period. The blood and organs of the experimental rats were collected and were subjected to hematological and biochemical analysis by following standard hospital protocols, after the treatment period. Results: After 30 days of fermentation, the pH of FMJ was reduced to 4.10 from 4.31. Lactobacillus load was increased gradually during fermentation while Bacillus spp. load decreased progressively, finally after 30 days of fermentation, no Bacillus spp., and yeast was found in FMJ. FMJ supplementation did not affect the body mass of experimental animals. The alternations in the organ weight were not associated with FMJ intervention. FMJ supplementation did not significantly affect the normal range of the selected hematological and biochemical parameters, which suggested that FMJ was not harmful to experimental rats. Conclusion: FMJ was enriched with lactic acid bacteria, and free from pathogenic microbes. FMJ was found as safe for rodent consumption without any adverse effects. Further, studies are needed to explain the beneficial effect of L. paracasei mediated FMJ.